2002
DOI: 10.1023/a:1014323009493
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic life events and suicide risk among jail inmates: The influence of types of events, time period and significant others

Abstract: Relationships between traumatic life events and suicide risk were studied in two samples of jail inmates with a low (N = 216) and a high (N = 51) suicide risk. Although nonsuicidal inmates reported a high prevalence of traumatic life events, suicidal inmates reported even higher prevalence rates. Suicidal inmates reported more episodes of sexual abuse, physical maltreatment, emotional maltreatment, abandonment, and suicide attempts by significant others. They also had experienced more traumatic life events dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
3
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 41 publications
6
82
3
3
Order By: Relevance
“…Most studies have confirmed that women are at high risk for suicidal behaviors during incarceration, and researchers have reported prevalence rates of 25% to 50% for prior suicide attempts in female prison samples (Blaauw, Arensman, Kraaij, Winkel, & Bout, 2002). Thus, this population of inmates is particularly worthy of study because of high rates of both self-harm and other-harm behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have confirmed that women are at high risk for suicidal behaviors during incarceration, and researchers have reported prevalence rates of 25% to 50% for prior suicide attempts in female prison samples (Blaauw, Arensman, Kraaij, Winkel, & Bout, 2002). Thus, this population of inmates is particularly worthy of study because of high rates of both self-harm and other-harm behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…These researchers did not examine the differential relationships between the two factors of the PCL-R and abuse. Preliminary research in men suggests that PCL-R F2, but not F1, is related generally to familial-environmental variables involving childhood adversity (Harpur et al, 1989).Abuse history may also play a role in the development of suicidality and self-harm behaviors across different populations (Arboleda-Florez & Wade, 2001;Johnson et al, 2002), including jail detainees (Blaauw et al, 2002) and female prisoners (Snow, 1997). In the current study, we examined the contribution of childhood abuse history to accounting for criminal and suicidal behaviors, and their co-occurrence, within a female prison sample.…”
mentioning
confidence: 99%
“…Enfin les événements traumatiques de vie tels que l'abus sexuel, la maltraitance physique et émotionnelle, l'abandon, les tentatives de suicide (soit pendant l'enfance, l'âge adulte ou la détention) sont associés à un risque suicidaire [3].…”
Section: Les Variables Personnelles Et Psychosocialesunclassified
“…The occurrence of suicidal behaviour also depends on type of negative life event, time of its appearance and support a person has in his environment, and can be part of a process triggered by a stressful event. Especially threatening are negative events that occur in childhood (2). An expanding body of research suggests that childhood trauma and adverse experiences can lead to a variety of negative health outcomes, including substance abuse, depressive disorders, and attempted suicide among adolescents and adults (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Especially threatening are negative events that occur in childhood (2). An expanding body of research suggests that childhood trauma and adverse experiences can lead to a variety of negative health outcomes, including substance abuse, depressive disorders, and attempted suicide among adolescents and adults (2)(3)(4). It was shown that childhood sexual and physical abuse are strongly associated with suicidal behaviour in adulthood (5).…”
Section: Introductionmentioning
confidence: 99%